Makers of modern dalit history - Ramabadran, Sudarshan; Paswan, Guru Prakash (Gurgaon Penguin Books, 2021)
In late-nineteenth-century Kerala, a man flamboyantly rode a villuvandi (bullock cart) along a road. What might sound like a mundane act was, at that time, a defiant form of protest. Riding animal-pulled vehicles was a privilege enjoyed only by the upper castes. This man, hailing from the untouchable Pulaya community, was attacking caste-based discrimination through his act. He was none other than Ayyankali, a social reformer and activist. Featuring several such inspiring accounts of individuals who tirelessly battled divisive forces all their lives, this book seeks to enhance present-day India's imagination and shape its perception of the Dalit community. Based on original research on historical and contemporary figures such as B.R. Ambedkar, Babu Jagjivan Ram, Gurram Jashuva, K.R. Narayanan, Soyarabai and Rani Jhalkaribai, among many others, Makers of Modern Dalit History will be a significant addition to the Dalit discourse. This definitive volume on some of the foremost Dalit thinkers, both past and present, promises to initiate a much-needed conversation around Dalit identity, history and politics.
Keywords: Social reformers